The role and value of fieldwork in library and information science education a case study of the LIS 181 (Field assignment) - Gelvezon, Lili Ann B.; Santos, Herminia H. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 2001)
Training programs such as fieldwork have reached an important place in the curriculum of almost any field of study, including Library and Information Science education. It is strongly held that making connections through fieldwork is the way to achieve the needed integration between theory and practice.
This study is an investigation on the role and value of LIS 181: Field Assignment in the Bachelor of Library and Information Science program of the Institute of Library Science. It also aims to find out: 1) how the Field Assignment is being conducted, 2) the students' evaluation of the Field Assignment, 3) the benefits that students and librarian-supervisors receive from the course, 4) the problems that they encounter, and 5) their recommendations for the improvement of the Field Assignment.
A case study approach was used involving 149 BLIS students who have taken LIS 181 from the first semester of AY 1997-1998 up to the first semester of AY 2000-2001. Unfortunately, only 97 or 65 percent of these students responded to the questionnaire. Twelve librarian-supervisors who handled practicum students from the said period were also interviewed. Six of these librarian-supervisors came from the UP Main Library, one from the UP Integrated School Library, one from the QC Public Library and four from special libraries, which were the ABS-CBN Tape Library, GMA Program Library and Media Archives, SSS Library, NIPAP Library.
The study found that majority of the student respondents place a high value on the Field Assignment approving that effectiveness and efficiency could be achieved through it. Most of them also expressed high degree of agreement regarding the benefits that they have received from the course. This also shows that the respondents view the Field Assignment as playing a number of important functions. However, some problems encountered in the Field Assignment were also expressed by the students as well as the librarian-supervisors. With this, they had also given a number of recommendations for the further improvement of the course. The survey data also showed that majority of the students preferred longer practicum hours divided into different types of libraries.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Librarians -- Philippines -- Quezon City; Library schools -- Curricula; Library science -- Field work; University of the Philippines Institute of Library Science Students